Increased peripheral inflammatory responses in myelin oligodendrocyte glycoprotein associated disease and aquaporin-4 antibody positive neuromyelitis optica spectrum disorder - Bauer, Angelika; Rudzki, Dagmar; Berek, Klaus; Dinoto, Alessandro; Lechner, Christian; Wendel, Eva-Maria; Hegen, Harald; Deisenhammer, Florian; Berger, Thomas; Höftberger, Romana; Rostasy, Kevin; Mariotto, Sara; et al. (Frontiers in Immunology, 2022)
Autoantibody-associated demyelinating diseases of the central nervous system such as myelin oligodendrocyte glycoprotein-antibody associated disease (MOGAD) and aquaporin 4-antibody positive neuromyelitis optica spectrum disorders (AQP4+ NMOSD) are rare diseases but can cause severe disability. In both diseases, associated neuroinflammation is accompanied by blood and cerebrospinal fluid cytokine and chemokine signatures, which were shown to be distinct from those observed in patients with multiple sclerosis (MS). In this study, we aimed to confirm and extend these findings by analyzing a larger number of serum cytokines, chemokines and related molecules in patients with MOGAD or AQP4+ NMOSD in comparison to MS, to better understand the pathophysiology and to identify biomarkers potentially useful in clinical practice for diagnostic and treatment purposes. A total of 65 serum cytokines, chemokines and related molecules like growth factors and soluble receptors were measured by Procartaplex multiplex immunoassays in 40 MOGAD, 40 AQP4+ NMOSD and 54 MS patients at baseline. Furthermore, follow-up samples of 25 AQP4+ NMOSD and 40 MOGAD patients were measured after 6-12 months. Selected analytes were validated in a subgroup of samples using other bead-based assays and ELISA. At baseline, 36 analytes in MOGAD and 30 in AQP4+ NMOSD were significantly increased compared to MS. K-means cluster analysis of all significantly altered molecules revealed three distinct groups: Cluster I, including 12 MOGAD, 2 AQP4+ NMOSD and 3 MS patients, had a specific association with 11 IL-6/IL-17A associated cytokines. In this cluster, 9/17 (53%) patients were children. Cluster II with 13 MOGAD, 24 AQP4+ NMOSD and 1 MS patient was associated with 31 upregulated analytes. Cluster III contained 15 MOGAD, 14 AQP4+ NMOSD and 50 MS patients. In cluster II and III the majority were adults (82% and 92%). Most measured analytes remained stable over time. Validation of selected cytokines and chemokines using other analytical methods revealed moderate to high correlation coefficients, but absolute values differed between assays. In conclusion, these results obtained by bead-based multiplex assays highlight a significant association of biomarkers of peripheral inflammation in patients with antibody-associated demyelinating diseases in comparison with MS.